2009 IEEE MTT-S International Microwave Symposium Digest 2009
DOI: 10.1109/mwsym.2009.5165858
|View full text |Cite
|
Sign up to set email alerts
|

SU-8 micromachining of millimeter and submillimeter waveguide circuits

Abstract: Micromachined WR 3.4 waveguide circuits are fabricated using a SU-8 micromachining process. In order to demonstrate the viability and repeatability of this process both straight waveguide sections and cylindrical cavity resonators are fabricated and measured. The SU-8 waveguide compares reasonably well to a standard WR 3.4 waveguide section. The measured cavity resonators demonstrate quality factors of 1900 and 2200 at a resonant frequency of 308 GHz.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…It is also interesting to note that the TINTIN consortium first reported the concept of SU-8 formed split-block waveguides, using their snap-together techniques, demonstrating a loss of ∼0.5 dB/λ g at W-band [15]. More recently, Smith et al [18] have demonstrated WR-3.4 band (220-330 GHz) split-block waveguides and cylindrical cavities. The most recently reported work on SU-8 formed split-block waveguides, from the University of Birmingham (U.K.), also showed impressive results at 60 GHz [19], 280 GHz [20], [21], and 650 GHz [22].…”
mentioning
confidence: 99%
“…It is also interesting to note that the TINTIN consortium first reported the concept of SU-8 formed split-block waveguides, using their snap-together techniques, demonstrating a loss of ∼0.5 dB/λ g at W-band [15]. More recently, Smith et al [18] have demonstrated WR-3.4 band (220-330 GHz) split-block waveguides and cylindrical cavities. The most recently reported work on SU-8 formed split-block waveguides, from the University of Birmingham (U.K.), also showed impressive results at 60 GHz [19], 280 GHz [20], [21], and 650 GHz [22].…”
mentioning
confidence: 99%
“…SU-8 photoresist is a promising technology for manufacturing millimeter and submillimeter waveguide components, and is used for the second filter discussed in this paper. SU-8 is a photolithographically patterned, epoxy-based, resin that is resistant to organic solvents once cured, and can have a thickness ranging from 0.5 µm to 1 mm [15]. There are several advantages of using SU-8 micromachining over CNC machining.…”
Section: Wr-3 Waveguide Bandpass Filters Fabricated Usingmentioning
confidence: 99%
“…It may also allow sharper internal corners and higher corner radius to depth ratios. Meanwhile, the SU-8 process is a batch fabrication which allows repeatability between devices as well as production of several devices in a single fabrication run [15]. Compared with DRIE, standard photolithography processes are used with SU-8 with better surface roughness on the sidewalls of waveguide structures [15].…”
Section: Wr-3 Waveguide Bandpass Filters Fabricated Usingmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of microwave circuits, including phase shifters [6], recongurable matching networks [7], and tunable lters [8] have all been demonstrated using RF MEMS devices. In addition MEMS fabrication techniques, known as micromachining, have been used to develop a variety of passive microwave components such as planar inductors and transformers, antennas, and guided wave structures [9,10]. The success of these devices has led to increased interest in using MEMS (and MEMS fabrication techniques) in RF and microwave systems.…”
Section: Rf Mems Technology and Applicationsmentioning
confidence: 99%